EFEKTIVITAS PENDEKATAN PROBLEM SOLVING DALAM PEMBINAAN KEAMANAN DAN KETERTIBAN MASYARAKAT DI POLSEK KAHU KABUPATEN BONE - Heriwati, Heriwati; Mahsyar, Abdul; Usman, Jaelan (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to find out the Effectiveness of the Problem Solving Approaches in Fostering Public order and Security at the Kahu Police station, Bone Regency. This study used a qualitative approach that provided an overview or phenomena and problems that occured. Data collection techniques were observation, media review, interviews and documentation. The results of this study showed the effectiveness of problem solving approaches in developing Kamtibmas, there were three criteria, namely: Goal Achievement, Integration and Adaptation. Based on the results of the study, it showed that the effectiveness of the Problem Solving Approach in the Guiding Kamtibmas in achieving the goals had run well and did not take a long time and it had reached the final goal of mediation. However, in the integration process, there were still people who did not know the forms of socialization carried out by Bhabinkamtibmas and did not know the existence of Bhabinkamtibmas in their villages.